Minimum Quality Threshold in Pre-Clinical Sepsis Studies (MQTiPSS): An International Expert Consensus Initiative for Improvement of Animal Modeling in Sepsis. Issue 4 (October 2018) - Osuchowski, Marcin F.; Ayala, Alfred; Bahrami, Soheyl; Bauer, Michael; Boros, Mihaly; Cavaillon, Jean-Marc; Chaudry, Irshad H.; Coopersmith, Craig M.; Deutschman, Clifford S.; Drechsler, Susanne; Efron, Philip; Frostell, Claes; et al.
Abstract : ABSTRACT: Preclinical animal studies precede the majority of clinical trials. While the clinical definitions of sepsis and recommended treatments are regularly updated, a systematic review of preclinical models of sepsis has not been done and clear modeling guidelines are lacking. To address this deficit, a Wiggers-Bernard Conference on preclinical sepsis modeling was held in Vienna in May, 2017. The goal of the conference was to identify limitations of preclinical sepsis models and to propose a set of guidelines, defined as the " Minimum Quality Threshold in Preclinical Sepsis Studies " (MQTiPSS), to enhance translational value of these models. A total of 31 experts from 13 countries participated and were divided into six thematic Working Groups: Study Design, Humane modeling, Infection types, Organ failure/dysfunction, Fluid resuscitation, and Antimicrobial therapy endpoints. As basis for the MQTiPSS discussions, the participants conducted a literature review of the 260 most highly cited scientific articles on sepsis models (2002–2013). Overall, the participants reached consensus on 29 points; 20 at "recommendation" and nine at "consideration" strength. This Executive Summary provides a synopsis of the MQTiPSS consensus. We believe that these recommendations and considerations will serve to bring a level of standardization to preclinical models of sepsis and ultimately improve translation of preclinical findings. These guideline points are proposed as "best practices" for animal models of sepsis that should be implemented. To encourage its wide dissemination, this article is freely accessible on the Intensive Care Medicine Experimental and Infection journal websites. In order to encourage its wide dissemination, this article is freely accessible in Shock, Infection, and Intensive Care Medicine Experimental .